The Upgrading of Woman Capabilities in Rural Areas to Implement Social Justice - Herdiansyah, Herdis; Nafi, Tien Handayani; Febriani, Rika (2016)
Gender inequality is closely related to poverty. When poverty combined with gender inequality resulting a failure in the main human capabilities. Custom can be as barrier to maximalize the woman performance outside the home.Traditional cultural practices that suppress women such as: early marriage and domestic violence comes from the view of the particular culture. Cultural particularism presupposes that a culture has its own system moral. In consequence, We can not use universal standard in assessing the culture because this claim. If we want to maintain a universal norms of human functions that include women as equal participants, we should be able to answer the claims that there is a universal value of humanity that we can use as a benchmark in community. With the use of a universal standard measure, the government expected can address the gender inequality that became one of the main problems in rural areas. This paper itself is based on the society engagement programme in X village, Tasikmalaya, Indonesia. This village has a strong cultural traditions that pose obstacles for woman to be flourishing. Therefore by empowering women through educate woman to get an alternative incomes actually can empower the community as a whole. Emotion intelligent and personality elements are closely associated with perception and decision making. Emotions allow for a thorough ethical vision. Vision of ethical life comes from human experience in a variety of cultures that appear in the question of how the good human life can be. Natural state of emotion that had been considered irrelevant in the decision turns out to be useful in performing social functions performed by women. By education, there’s advantage for woman to get her capabilities right and find herself value in society. We believe that good government also can facilitate the formation of good capabilities and provide means for their use. Right to get education and material support can makes woman fully capable in the major human functions.